Electroacupuncture at HT5 + GB20 promotes brain remodeling and significantly improves swallowing function in patients with stroke - Fu, Xuefeng; Li, Hao; Yang, Wen; Li, Xuezheng; Lu, Lijun; Guo, Hua; Guo, Kaifeng; Huang, Zhen (Frontiers in Neuroscience, 2023)
Background This study compared the differences in the degree of brain activation, and swallowing function scales in patients with post-stroke dysphagia after treatment. We explored the mechanism of cortical remodeling and the improvement effect of electroacupuncture on swallowing function in patients and provided a theoretical basis for the clinical application of electroacupuncture. Methods Fifty patients with post-stroke dysphagia were randomized to the control or electroacupuncture group. The control group underwent conventional swallowing rehabilitation for 30 min each time for 12 sessions. In the electroacupuncture group, electroacupuncture was performed based on conventional swallowing rehabilitation for 30 min each time for 12 sessions. Cortical activation tests and swallowing function assessments were performed before and after treatment. Statistical analyses were used to investigate the differences within and between the two groups to explore the treatment effects. Results There were no statistical differences in clinical characteristics and baseline data between the two groups before treatment. Cortical activation and swallowing function were improved to different degrees in both groups after treatment compared with before treatment. After treatment, the electroacupuncture group showed higher LPM (t = 4.0780, p < 0.001) and RPM (t = 4.4026, p < 0.0001) cortical activation and tighter functional connectivity between RS1 and LM1 (t = 2.5336, p < 0.05), RM1 and LPM (t = 3.5339, p < 0.001), RPM and LM1 (t = 2.5302, p < 0.05), and LM1 and LPM (t = 2.9254, p < 0.01) compared with the control group. Correspondingly, the improvement in swallowing function was stronger in the electroacupuncture group than in the control group (p < 0.05). Conclusion This study demonstrated that electroacupuncture based on conventional treatment activated more of the cerebral cortex associated with swallowing and promoted functional connectivity and remodeling of the brain. Accompanying the brain remodeling, patients in the electroacupuncture group also showed greater improvement in swallowing function. Clinical trial registration ClinicalTrials.gov, ChiCTR2300067457.